Finnish graduated physics teachers' views about their teacher education program - The disparity between the needs and delivery - Risto Leinonen; Markku Haaranen; Mikko Kesonen; Mika Koponen; Pekka E. Hirvonen; Mervi A. Asikainen (OmniaScience, 2020)
In this article, graduated physics teachers' views about their teacher education program and professional needs are evaluated. With respect to teacher knowledge, Physical Knowledge for Teaching (PKT) framework consisting of six domains related to content knowledge and pedagogical content knowledge was developed based on the framework of Mathematical Knowledge for Teaching. PKT was utilized in the design of a Likert scale instrument that aims to discover teachers' views concerning these six domains from two separate viewpoints: to what extent the domains were covered in their teacher education program concerning the domains, and how important is that theme for their profession. Results revealed that teachers see that the domains related to common content knowledge and structures of physics have been addressed adequately in their teacher education but characteristics of other domains, such as teaching methods, evaluation, and motivating learners, received less favorable evaluations. With respect to the importance of different domains for teacher profession, teachers valued the importance of every domain of teacher knowledge highly. These findings suggest that the greatest deficiencies in this physics teacher education program lie on addressing pedagogical content knowledge with its various sub-domains. Our PKT framework offers a promising base for evaluating physics teacher knowledge. We suggest that a framework for teacher knowledge should be explicitly introduced for pre-service teachers in their education so that they could evaluate their knowledge and professional needs better.